The Role Of The Marketing Information Quality In Customer Relationship Management - أحمد, أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed to analyze the quality of marketing information in the Commercial Bank of Syria, to identify the indicators of managing the relationship with the customer, and to determine the nature of the relationship between the quality of marketing information and the management of the relationship with the customer. Clarify the factors influencing this relationship, and propose the optimal model for them. In order to achieve this, the researcher proceeded to formulate a basic hypothesis which is divided into three hypotheses. The researcher adopted the survey method using the questionnaire to collect data from the study community composed of the customers of the Commercial Bank of Syria. Data were analyzed by statistical package for statistical sciences, The researcher used many statistical methods, the most important of which are: arithmetic mean, standard deviation of sample, relative importance, variation coefficient, single sample t test, multiple linear regression, legal correlation analysis. The researcher reached a number of results, the most important of which are: The existence of an acceptable relationship of statistical significance between the dimensions of the quality of marketing information and customer satisfaction in the Commercial Bank of Syria, and the existence of a strong relationship of statistical significance between the dimensions of the quality of marketing information and customer loyalty in the bank, and the existence of an acceptable relationship of statistical significance between the dimensions of the quality of marketing information and customer value in the bank, The researcher also found a strong correlation between the dimensions of the quality of marketing information and customer relationship management indicators in the Commercial Bank of Syria. The researcher advise for the important of working in bank based on total quality management and dealing with marketing information system as primary role and supplying materiality and incorporeity supporting from bank management for marketing information system development for all its objects.